Mind the Gap: Successful Endoscopic Closure of a Large Gastric Sleeve Leak Using an Endoscopic Stent and Over-the-Scope Clips - Jiannis Anastasiou (Case Reports in Gastroenterology, 2017)
Laparoscopic sleeve gastrectomy (LSG) is gaining popularity for the treatment of morbid obesity. It is regarded as a simple, low-cost procedure achieving significant weight loss within a short period of time. LSG is considered a safe procedure with a relatively low complication rate. The complications encountered nevertheless can result in significant morbidity and may even be lethal. The most significant complications are staple-line bleeding, stricture, and staple-line leak. The purpose of this paper is to present a case of a 31-year-old patient complicated by a 3.06 cm staple-line leak 10 days after LSG. Review of the current literature regarding this complication as well as outline of a strategy for the management of large post-LSG gastric leaks is suggested.